Integrating sustainability in dentistry: a pathway towards achieving the UN 2030 agenda - Guerra, Matilde; Morgado, Mariana; Leira, Yago; Leitão, Tiago; Botelho, João; Mendes, José João (Frontiers in Oral Health, 2025)
The growing impact of the climate crisis has raised significant concerns due to its profound effects on public health and ecological stability. This article explores how the implementation of sustainable practices in dentistry can contribute to a more efficient, safe and environmentally responsible approach, in line with the Sustainable Development Goals outlined in the United Nations’ 2030 Agenda. A key focus is on waste reduction, which is achieved through the promotion of oral health and disease prevention, thereby minimising the waste and carbon emissions associated with dental care. In addition, the responsible use of resources such as water and energy and the use of environmentally sustainable dental materials play a critical role in reducing the environmental footprint of dentistry. Key measures such as the recycling of single-use plastics are essential to curb pollution and reduce the uptake of microplastics by marine ecosystems and humans. Education and awareness of sustainability is also essential. This can be promoted by integrating sustainable principles into the curriculum of dental courses and within scientific committees. Promoting these practices among emerging health professionals and researchers will drive the development of innovative alternatives that further reduce the environmental impact of the field.